Modeling and control of induction motors - Delaleau, Emmanuel; Louis, Jean-Paul; Ortega, Romeo (Zielona Góra: Uniwersytet Zielonogórski)
This paper is devoted to the modeling and control of the induction motor. The well-established field oriented control is recalled and two recent control strategies are exposed, namely the passivity-based control and the flatness-based control.
Keywords: induction motors; field oriented control; passivity based control; flatness based control; nonlinear control